Implementasi Activity Based Management dalam Meningkatkan Efisiensi Biaya Pelayanan Rawat Inap di RS X Kabupaten Pamekasan - Prasetyo, Seto Wahyu; Bayangkara, Ida Bagus Ketut; Riyadi, Slamet (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
One of the strategies to survive in business competition is to control operational costs. The activity-based management method emerged as an appropriate activity management approach in making decisions related to cost reduction. With the various types of services provided, RS X Pamekasan Regency needs to make cost efficiency through reducing non-value-added activities. This study aims to analyse cost efficiency using the activity-based management method to obtain accurate cost information, so as to identify and reduce inefficient activities, and provide recommendations for cost efficiency policies. The methodology used is qualitative with a case study approach, using data collection techniques through documentation, interviews, and observations. Analysis of cost efficiency calculations using activity-based management. The research findings revealed that the implementation of activity-based management successfully identified activities that need to be maintained because they provide added value, as well as activities that do not add value. However, RS X Pamekasan Regency has not been able to implement activity based management optimally due to the limited resources it has.